Anorexia nervosa: Gut microbiota-immune-brain interactions - Roubalová, Radka; Procházková, Petra; Papežová, Hana; Smitka, Kvido; Bilej, Martin; Tlaskalová-Hogenová, Helena (Clinical nutrition, 2020)
Anorexia nervosa is a psychiatric disorder defined by an extremely low body weight, a devastating fear of weight gain, and body image disturbance, however the etiopathogenesis remains unclear. The objective of the article is to provide a comprehensive review on the potential role of gut microbiota in pathogenesis of anorexia nervosa. Recent advances in sequencing techniques used for microbial detection revealed that this disease is associated with disruption of the composition of normal gut microbiota (dysbiosis), manifested by low microbial diversity and taxonomic differences as compared to healthy individuals. Microorganisms present in the gut represent a part of the so called "microbiota-gut-brain" axis that affect the central nervous system and thus human behavior via the production of various neuroactive compounds. In addition, cells of the immune system are equipped with receptors for these neuroactive substances. Microbiota of the intestinal system also represent a very important antigenic source. These antigens can mimic some host neuropeptides and neurohormones and thus trigger the production of autoantibodies which cross-react with these compounds. The levels and affinities of these antibodies are thought to be associated with neuropsychiatric conditions including anxiety, depression, and eating and sleep disorders. The study of microbiota function in diseases could bring new insights to the pathogenetic mechanisms.
Keywords: Anorexia Nervosa; lidé; mentální anorexie; Brain; mozek; Humans